2020
DOI: 10.1016/j.radonc.2019.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of internal target volume definition for pencil beam scanned proton treatment planning in the presence of respiratory motion variability for lung cancer: A proof of concept

Abstract: Impact of internal target volume definition for pencil beam scanned proton treatment planning in the presence of respiratory motion variability for lung cancer: a proof of concept. Radiotherapy and Oncology, 145,[154][155][156][157][158][159][160][161]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…4D MIB optimization is often restricted to a few 4DCT phases or a single 4DCT scan as motion surrogate. Several studies have highlighted the impact of variability in the motion patterns on various timescales, during and between treatment fractions [76], [53], [77], [28], [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4D MIB optimization is often restricted to a few 4DCT phases or a single 4DCT scan as motion surrogate. Several studies have highlighted the impact of variability in the motion patterns on various timescales, during and between treatment fractions [76], [53], [77], [28], [25].…”
Section: Discussionmentioning
confidence: 99%
“…Bernatowicz et al suggested using four-dimensional computed tomography-magnetic resonance imaging (4DCT-MRI) that combines patient 4DCT with motion information extracted from multi-respiratory cycle 4DMRI [26]. Krieger et al proposed to consider variable respiration from 4DMRI to generate a probabilistic ITV, so that the dose to healthy tissues can be significantly reduced [27]. This combination allows the creation of multi-respiratory cycle 4DCTs.…”
Section: Number Of Images / Motion Samplingmentioning
confidence: 99%
“…Time-resolved 4DCT(MRI) were employed to simulate motion variabilities over a comprehensive time duration of up to 11 min using two different 4DMRI approaches. To take these motion variabilities into account for treatment planning, a recently presented probabilistic ITV definition was applied (Krieger et al 2020) and two-field SFUD plans were optimised on composite planning CTs. Good geometrical and dosimetric agreement were achieved, however, with a tendency of higher geometrical errors for the 4DMRI based on slice stacking when compared to the patch registration approach.…”
Section: Discussionmentioning
confidence: 99%
“…Motion variabilities can be acquired using 4DMRI as described in the previous subsection. In order to combine these two types of information, synthetic 4DCT(MRI) data sets as described by Boye, Samei, Schmidt, Székely & Tanner (2013), Zhang et al (2016) and Krieger et al (2020) were generated. DVFs extracted from the five 4DMRI data sets were matched to the full-exhale CT scans ‡ www.plastimatch.org, accessed: 13.01.2020…”
Section: Dct(mri)mentioning
confidence: 99%
“…Finally, since we used only one 4DCT dataset per patient, respiratory variability is not accounted. Respiratory variability has been reported to significantly influence the target coverage, and could be handled with probabilistic ITV approach based on four-dimensional MRI [43]. Although this approach is effective, it requires clinical resources, such as MRI acquisition over multiple respiratory cycles.…”
Section: Study Limitationsmentioning
confidence: 99%